1991
DOI: 10.1080/10412905.1991.9697979
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Different Irrigation Practices Used forMentha piperitain Bulgaria

Abstract: Publication details, including instructions for authors and subscription information:ABSTRACT: In Bulgaria, peppermint (Mentha piperita L.) must be grown under irrigation if high yields of oil and leaves are to be realized. To determine the most efficient and beneficial irrigation system, the effect of sprinkler irrigation, surface drip irrigation, subsurface irrigation at 35 cm depth and subsurface irrigation with microporous hose at 15 cm depth on peppermint culture over a four-year period was evaluated. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…It has been reported that the essential oil accumulation in peppermint could be influenced by environmental factors such as photoperiod (Clark and Menary, 1979b), Menary, 1980a, 1980b), light (Burbott and Loomis, 1967), and agronomic factors such as soil amendments, nutrients, or trace elements (Alkire and Simon, 1995;Mustiatse, 1985;Nedkov and Georgiev, 1991;Scavroni et al, 2005;Zheljazkov, 2005;Zheljazkov and Margina, 1996;Zheljazkov and Nielsen, 1996). Nitrogen is one of the most important modifiers of peppermint productivity and oil composition (Clark and Menary, 1980c;Jeliazkova et al, 1999;Kothari and Singh, 1995;Mitchell and Farris, 1996;Piccaglia et al, 1993;Singh et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the essential oil accumulation in peppermint could be influenced by environmental factors such as photoperiod (Clark and Menary, 1979b), Menary, 1980a, 1980b), light (Burbott and Loomis, 1967), and agronomic factors such as soil amendments, nutrients, or trace elements (Alkire and Simon, 1995;Mustiatse, 1985;Nedkov and Georgiev, 1991;Scavroni et al, 2005;Zheljazkov, 2005;Zheljazkov and Margina, 1996;Zheljazkov and Nielsen, 1996). Nitrogen is one of the most important modifiers of peppermint productivity and oil composition (Clark and Menary, 1980c;Jeliazkova et al, 1999;Kothari and Singh, 1995;Mitchell and Farris, 1996;Piccaglia et al, 1993;Singh et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…The essential oil content and composition of peppermint are important economically for producers, processors, manufacturers of peppermint-containing products, and for consumers. Prior research has shown that environmental factors such as harvest date and photoperiod Menary, 1979a, 1979b), latitude and growing conditions (Topalov, 1962), soil contamination (Zheljazkov et al, 2006;Zheljazkov and Nielsen, 1996), soil amendments (Zheljazkov, 2005;Zheljazkov and Warman, 2004), and agronomic practices such as harvest stage (Clark and Menary, 2006), irrigation (Nedkov and Georgiev, 1991;Ram et al, 1995;Topalov, 1962), pesticide application (Zheljazkov and Margina, 1996), or fertilization (Mitchell and Farris, 1996;Scavroni et al, 2005;Topalov, 1962) influence peppermint essential oil content and composition. The climate in the northwestern United States is considered suitable for the production of high-quality peppermint essential oil.…”
mentioning
confidence: 99%
“…Hazra et al (1990) indicated that drying in direct sunlight needs 24 % less steam than required during distillation. Nedkov and Georgiev (1991) said that spearmint, is a major essential oil plant. Dried leaves are used for various blends of tea which are reputed to have medicinal properties.…”
Section: Introductionmentioning
confidence: 99%